GAMBARAN TREN PENYAKIT CAMPAK DI PUSKESMAS WILAYAH KERJA DINAS KESEHATAN KOTA TANGERANG TAHUN 2013-2015 - Irna Novianty; Khilda Fajriyati; Nur Annisa Fajri; Izza Suraya (UHAMKA Press, 2016)
Description of Measles Trend on Tangerang City Between 2013 and 2015Introduction. A Case Based Measles Surveillance (CBMS) has been implemented since 2007 atthe Puskesmas level and in 2011 at the provincial level. The purpose of this study is to find out thedescription of measles trends in 30 health centers coverage Dinas Kesehatan Kota Tangerang(Tangerang City Health Service) period 2013 to 2015 after CBMS applied. Methods. This research uses descriptive method. The analysis used is univariate analysis withsecondary data source. Based on the inclusion criteria, people who suspect measles and visited the30 primary health care that Dinas Kesehatan Kota Tangerang area, the sample in 2013 is 810respondents, in 2014 is 561 respondents, and in 2015 is 486 respondents. Data was collected bycollecting C-1 Individual Measles Case reports was reported by each rimary Health Care.Results. In 2013, there were 43 cases of measles from 810 people (41.7%). In 2014, a number of17 cases from 561 (13,65) was found.. In the last period, there were 14 cases from 486 people(8,2%). Conclusion. Thus, there were declining on measles incidence in the Tangerang City HealthService between 2013 and 2015.Trend, Campak, CBMS